Climate change and individual behavior - René Bernard; Panagiota Tzamourani; Michael Weber (Deutsche Bundesbank, 2022)
This paper studies the causal effect of providing information about climate changeon individuals' willingness to pay to offset carbon emissions in a randomizedcontrol trial. Receiving truthful information about ways to reduce CO2 emis-sions increases individuals' willingness to pay for CO2 offsetting relative to thecontrol group. Individuals receiving information about the behavior of peersreact similarly to those receiving information about scientific research. Individ-uals' responses vary depending on their socio-demographic characteristics andalso along a rich set of prior beliefs and concerns regarding climate change. Ina follow-up survey, we study the endogenous information acquisition of surveyparticipants and show that individuals choose information that aligns with theirviews. Individuals who choose to receive information about climate changehave a higher willingness to pay for CO2 offsets.
Keywords: D10; D83; D91; Q54; 330; Climate change; information treatment; willingness to pay; CO2 compensation; information acquisition